Low Velocity Impact and Creep-Strain Behaviour of Vinyl Ester Matrix Nanocomposites Based on Layered Silicate - A. I. Alateyah; H. N. Dhakal; Z. Y. Zhang; B. Aldousiri (International Journal of Polymer Science)
The impact properties of neat vinyl ester and the nanocomposites were performed using a low velocity impact testing. The addition of layered silicate into the polymer matrix shows that an optimum range of nanoclay reinforcement in the vinyl ester matrix can produce enhanced load bearing and energy absorption capability compared to the neat matrix. In addition, the amount of microvoids in the nanocomposites structure influences the overall properties. Likewise, the influence of the clay addition into the neat polymer on the creep relaxation behaviour at 25°C and 60°C was studied. In both cases, the presence of the layered silicate remarkably improved the creep behaviour. The improvement of these properties can be assigned to the stiff fillers and the configurational linkage between the polymer and the layered silicate which are supported by scanning electron microscopy (SEM) and transmission electron microscopy (TEM) characterisations by showing a distinct change in surface morphology associated with improved impact toughness and creep response.